n = 1 ∑ ∞ ⌊ 4 n ⌉ 7 1
The above sum can be expressed as b a π α + d c π β , where a , b , c , d , α , and β are positive integers, with a and b being co-prime, c and d are co-prime.
Find a + b + c + d + α + β .
Details and Assumptions :
∙ ⌊ x ⌉ denotes the nearest integer to x .
Try my other calculus challenges here
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used the general expression of nint function.
S N ( s ) = n = 1 ∑ ∞ ( ⌊ n 1 / N ⌉ ) s 1
Expressions are available for s > 3
I also used . S 4 ( s ) = 4 ζ ( s − 3 ) + ζ ( s − 1 )
For s = 7 , we have = 4 5 2 π 4 + 9 4 5 π 6
Thanks for sharing that! That's the first time I hear about the this Formula, do you think there exist a closed form for S N ( s ) ??.
Log in to reply
Not a general closed form actually..
but it has closed forms for differnt N and s
and i love the way you present your solution.. U latex master :D !!!!
Log in to reply
And a genius like you,, may derive the closed form .
but i havent actually studied and read it anywhere yet. :) :) :)
Log in to reply
@Aman Rajput – Thanks my friend ! I will Check it out sometime. :) :)
Problem Loading...
Note Loading...
Set Loading...
First note that for a certain integer k :
⌊ x ⌉ = { k k + 1 if x ∈ [ k , k + 0 . 5 ) if x ∈ ( k + 0 . 5 , k + 1 ]
Let k ≤ 4 n < k + 1
Where k is an integer ranging between 1 and ∞ .
Let us split the interval into two :
k ≤ 4 n < k + 0 . 5 and k + 0 . 5 < 4 n < k + 1
Note that we restricted the value at k + 0 . 5 , since 4 n is either irrational or integral. Now rewrite the intervals as:
k 4 ≤ n < ( k + 0 . 5 ) 4 and ( k + 0 . 5 ) 4 < n < ( k + 1 ) 4
n is an integer , so rewrite as:
k 4 ≤ n ≤ ⌊ ( k + 0 . 5 ) 4 ⌋ and ⌈ ( k + 0 . 5 ) 4 ⌉ ≤ n < ( k + 1 ) 4
Therefore our Sum can be written as :
S = n = 1 ∑ ∞ ⌊ 4 n ⌉ 7 1
= k = 1 ∑ ∞ ( n = k 4 ∑ ⌊ ( k + 0 . 5 ) 4 ⌋ k 7 1 + n = ⌈ ( k + 0 . 5 ) 4 ⌉ ∑ ( k + 1 ) 4 − 1 ( k + 1 ) 7 1 )
The work inside the brackets is easy (as we have no n ):
S = k = 1 ∑ ∞ ( k 7 ⌊ ( k + 0 . 5 ) 4 ⌋ − k 4 + 1 + ( k + 1 ) 7 ( k + 1 ) 4 − 1 − ⌈ ( k + 0 . 5 ) 4 ⌉ + 1 )
Note that we should find an expression for ⌊ ( k + 0 . 5 ) 4 ⌋ :
( k + 0 . 5 ) 4 = k 4 + 2 k 3 + 2 3 k 2 + 2 1 k + 1 6 1
= k 4 + 2 k 3 + 2 k ( 3 k + 1 ) + 1 6 1
For any integral k , either k or 3 k + 1 will be even, hence :
2 k ( 3 k + 1 ) is an integer
And so :
⌊ ( k + 0 . 5 ) 4 ⌋ = ( k + 0 . 5 ) 4 − 1 6 1
Consequently:
⌈ ( k + 0 . 5 ) 4 ⌉ = ( k + 0 . 5 ) 4 − 1 6 1 + 1
Now back to our sum:
S = k = 1 ∑ ∞ ( k 7 ( k + 0 . 5 ) 4 − 1 6 1 − k 4 + 1 + ( k + 1 ) 7 ( k + 1 ) 4 − 1 − ( k + 0 . 5 ) 4 + 1 6 1 )
= k = 1 ∑ ∞ k 7 ( k + 0 . 5 ) 4 − 1 6 1 − k 4 + 1 + k = 1 ∑ ∞ ( k + 1 ) 7 ( k + 1 ) 4 − 1 − ( k + 0 . 5 ) 4 + 1 6 1
Now shift the index of the second series by one:
= k = 1 ∑ ∞ k 7 ( k + 0 . 5 ) 4 − 1 6 1 − k 4 + 1 + k = 2 ∑ ∞ k 7 k 4 − 1 − ( k − 0 . 5 ) 4 + 1 6 1
Note that the second series is zero at k = 1 :
= k = 1 ∑ ∞ k 7 ( k + 0 . 5 ) 4 − 1 6 1 − k 4 + 1 + k = 1 ∑ ∞ k 7 k 4 − 1 − ( k − 0 . 5 ) 4 + 1 6 1
= k = 1 ∑ ∞ ( k 7 ( k + 0 . 5 ) 4 − 1 6 1 − k 4 + 1 + k 7 k 4 − 1 − ( k − 0 . 5 ) 4 + 1 6 1 )
= k = 1 ∑ ∞ k 7 ( k + 0 . 5 ) 4 − ( k − 0 . 5 ) 4
= k = 1 ∑ ∞ k 7 4 k 3 + k
= 4 k = 1 ∑ ∞ k 4 1 + k = 1 ∑ ∞ k 6 1
= 4 ζ ( 4 ) + ζ ( 6 )
S = 4 5 2 π 4 + 9 4 5 1 π 6